Music, language, and human evolution - Bannan, Nicholas (Oxford University Press, 2012)
Examining the potential role of musicality in human evolution and its consequences for human culture, this book draws on archaeology, anthropology, psychology and musicology in order to illustrate the interdisciplinary necessity of accounting for the phenomenon of human music-making.